Characterization and Evaluation of Chicken Eggshell for use as a Bio-Resource - Ajala, E.O.; Eletta, O.A.A.; Ajala, M.A.; Oyeniyi, S.K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Chemical compositions of chicken eggshell were determined with the aim of finding economic uses for it; instead of becoming a nuisance to the environment. The concentrations obtained were (mg/L): calcium 2300.33 ± 3.80, magnesium 850.00 ± 1.24, sodium 33.83 ± 0.72, potassium 17.06 ± 1.04, iron 1.4 ± 0.03, zinc 0.99 ± 0.04 and copper 0.063 ± 0.01. The proximate showed that the eggshell contained, 0.95 ± 0.89, moisture; 45.29 ± 0.06, ash; 1.40 ± 0.25, crude protein; 0.37 ± 0.06, lipid; 4.38 ± 0.32, crude fibre; 47.63 ± 0.32 (%), carbohydrate and 811 ± 12.71 (cal/g), calorific value. Further analysis revealed the presence of carbon and oxygen in the eggshell in right proportion as a good alternative adsorbent for removal of heavy metals and dyes from aqueous solutions. Findings from the study shows that the chicken eggshell potentially represents a natural source of food nutrients.